2020
DOI: 10.1109/access.2020.2991382
|View full text |Cite
|
Sign up to set email alerts
|

In-Hand Sliding Regrasp With Spring-Sliding Compliance and External Constraints

Abstract: We investigate in-hand regrasping by pushing an object against an external constraint and allowing sliding at the fingertips. Each fingertip is modeled as attached to a multidimensional spring mounted to a position-controlled anchor. Spring compliance maps contact forces to spring compressions, ensuring the fingers remain in contact, and sliding ''compliance'' governs the relationship between sliding motions and tangential contact forces. A spring-sliding compliant regrasp is achieved by controlling the finger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Given knowledge of object dynamics, robots can perform accurate and robust multi-contact manipulation of modeled objects via physics-based planning and control [11][12][13][14][15][16][17][18]. Physically realistic simulation could also benefit from realworld object dynamics knowledge to train policies in simulation that robustly transfer to real systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given knowledge of object dynamics, robots can perform accurate and robust multi-contact manipulation of modeled objects via physics-based planning and control [11][12][13][14][15][16][17][18]. Physically realistic simulation could also benefit from realworld object dynamics knowledge to train policies in simulation that robustly transfer to real systems.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from inertial parameters, friction also plays an important role in contact-based object interaction such as in grasp planning via force-closure optimization [33] and sliding based in-hand manipulation [17]. Empirical studies of planar manipulation have also shown friction to play a key role in how objects react to contact [16,34].…”
Section: Introductionmentioning
confidence: 99%